2006
DOI: 10.1016/j.ejcts.2006.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life following off-pump versus on-pump coronary artery bypass grafting in elderly moderate to high-risk patients: a randomized trial

Abstract: Both on-pump and off-pump patients improved in health-related quality of life scores after CABG surgery. No clinically relevant difference between the groups could be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 30 publications
5
50
0
2
Order By: Relevance
“…The fact that G1 patients had higher incidence of stroke in the immediate postoperative period may lead to greater impairment of brain functions and have an impact on the quality of life reported by patients. This observation is consistent with those made by Motallebzadeh et al [1] and Jensen et al [3], whereby the qualities of life are better in both groups, without distinction between them.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The fact that G1 patients had higher incidence of stroke in the immediate postoperative period may lead to greater impairment of brain functions and have an impact on the quality of life reported by patients. This observation is consistent with those made by Motallebzadeh et al [1] and Jensen et al [3], whereby the qualities of life are better in both groups, without distinction between them.…”
Section: Discussionsupporting
confidence: 82%
“…Comparative studies using these two methods showed that both present similar results regarding the improved quality of life [1][2][3][4] and the patency of the graft [2,3,5], while several studies have shown some advantages without the use of CPB as lower risk of stroke (CVA), decreased incidence of atrial fibrillation and surgical wound infections [6].…”
Section: Introductionmentioning
confidence: 92%
“…6 Studies comparing self-assessed symptoms and quality of life (QoL) in younger patients have failed to show a significant benefit of 1 method over another. [11][12][13][14] Age is an independent predictor of major complications after cardiac surgery. Several authors have claimed that the benefits of OPCAB are more pronounced in elderly patients and patients with high comorbidity.…”
Section: Clinical Perspective On P 2439mentioning
confidence: 99%
“…In this questionnaire eight scales cover physical, mental, and social well-being (28). One study found a significantly higher score among CCABG-patients in one of the eight scales ("Role emotional") in contrast to another study who favoured OPCAB patients in the dimension "Social Relationships", using another questionnaire (29,30). In general, few significant inter-group differences have been found, given the multiple tests being performed.…”
Section: Quality Of Lifementioning
confidence: 82%